2018
DOI: 10.22606/mcmr.2018.23001
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Medicinal Plants Used in the Management of HIV/AIDs Opportunistic Infections in Njeru Sub County, Buikwe District

Abstract: Infectious diseases such as skin infection, chronic cough, stomach infection, tuberculosis, diarrhoea, warts, herpes zoster and others were claimed to be treated using medicinal plants. The study was aimed at determining the antibacterial activity and determination of bioactive compound of some medicinal plants used in management of HIV/AIDS opportunistic infections. A total of six plants were subjected to phytochemical and three out of six were tested against bacterial pathogens. The aqueous extracts of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The antibacterial activity of P. microcarpa (stem bark) aqueous extract (AI = 0.63) recorded in the present study was higher compared to that reported by Shehu et al (2018) in aqueous leaf extract (AI = 0.32) against S. aureus. Nevertheless, low concentration (90 mg mL -1 ) was used in their study compared to that used in the present study (100 mg mL -1 ), and this can account for the difference.…”
Section: Results and Discussion Antibacterial Activities Of Aqueous A...contrasting
confidence: 83%
“…The antibacterial activity of P. microcarpa (stem bark) aqueous extract (AI = 0.63) recorded in the present study was higher compared to that reported by Shehu et al (2018) in aqueous leaf extract (AI = 0.32) against S. aureus. Nevertheless, low concentration (90 mg mL -1 ) was used in their study compared to that used in the present study (100 mg mL -1 ), and this can account for the difference.…”
Section: Results and Discussion Antibacterial Activities Of Aqueous A...contrasting
confidence: 83%